1988
DOI: 10.1152/ajpregu.1988.254.2.r161
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and renal effects of low-dose infusions of atrial peptide in awake dogs

Abstract: The effects of alpha-human atrial natriuretic peptide (alpha-hANP) on cardiovascular and renal function in conscious dogs were evaluated in two experimental protocols. In one protocol, alpha-hANP was infused intravenously at increasing rates of 50, 100, and 200 ng.min-1.kg-1 (stepup infusion) during successive 20-min periods. The greatest responses occurred during the final 20-min period of the stepup infusion when the plasma concentration of immunoreactive atrial natriuretic peptide (irANP) was increased by 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
2

Year Published

1990
1990
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 0 publications
6
23
2
Order By: Relevance
“…Bie et al (26) reported that the comparable rise in plasma ANP to the present study gave rise to an increase in urinary Na' excretion (less than 2-fold) in euhydrated conscious dogs. Weidman et a/.…”
Section: Discussionsupporting
confidence: 76%
“…Bie et al (26) reported that the comparable rise in plasma ANP to the present study gave rise to an increase in urinary Na' excretion (less than 2-fold) in euhydrated conscious dogs. Weidman et a/.…”
Section: Discussionsupporting
confidence: 76%
“…It has also been reported that highdose ANF infusion in normovolemic animals induces only modest natriuresis. 3 The suppressed natriuresis in response to high-dose ANF infusions may similarly have resulted from the chloride-mediated feedback mechanism, in which a decreased tubular chloride concentration after acute ANF natriuresis may have prevented further natriuresis by inhibiting binding of ANF to its receptor.…”
Section: Misono Chloride-mediated Feedback Control Of Anf Receptormentioning
confidence: 99%
“…1,2 For example, infusion of ANF in normovolemic animals to mimic endogenous ANF increase on a high-salt diet fails to induce comparable natriuresis. 3 In edematous disease states such as congestive heart failure, 4,5 nephrotic syndrome, 5 and liver cirrhosis, 6 plasma ANF levels are elevated, yet sodium is retained. In addition, transgenic animals overexpressing ANF, with plasma ANF levels elevated 10-fold or more, maintain normal salt excretion.…”
mentioning
confidence: 99%
“…4 The increased PRA may be due to continuous relief from the direct suppression by ANP. 19 Furthermore, ANP acts within the kidney to increase GFR 6,20,21 and to decrease proximal sodium and water reabsorption via both inhibition of angiotensin-stimulated transport and a dopamine mediated mechanism. 22,23 The administration of HS-142-1 may decrease sodium delivery to macula densa.…”
Section: Plasma Hormonal Changesmentioning
confidence: 99%
“…Pharmacological doses of ANP increased excretion of water and sodium, associated with a significant increase in GFR. 6,20 Bolus administration of HS-142-1 reduced urine flow rate and urinary sodium excretion rate in advanced HF. 4 Furthermore, we observed the tendency to a decrease in urine flow rate and urinary sodium excretion rate following bolus administration of HS-142-1 in early-stage HF.…”
Section: Changes In Renal Functionsmentioning
confidence: 99%